Effects of Site-Directed Mutagenesis of Cysteine on the Structure of Sip Proteins - Wang, Lin; Ding, Ming-Yue; Wang, Jing; Gao, Ji-Guo; Liu, Rong-Mei; Li, Hai-Tao (Frontiers in Microbiology, 2022)
Bacillus thuringiensis, a gram-positive bacteria, has three insecticidal proteins: Vip (vegetative insecticidal protein), Cry (crystal), and Sip (secreted insecticidal protein). Of the three, Sip proteins have insecticidal activity against larvae of Coleoptera. However, the Sip1Aa protein has little solubility in the supernatant because of inclusion bodies. This makes it more difficult to study, and thus research on Sip proteins is limited, which hinders the study of their mechanistic functions and insecticidal mechanisms. This highlights the importance of further investigation of the Sip1Aa protein. Disulfide bonds play an important role in the stability and function of proteins. Here, we successfully constructed mutant proteins with high insecticidal activity. The tertiary structure of the Sip1Aa protein was analyzed with homologous modeling and bioinformatics to predict the conserved domain of the protein. Cysteine was used to replace amino acids via site-directed mutagenesis. We successfully constructed Sip149-251, Sip153-248, Sip158-243, and Sip178-314 mutant proteins with higher solubility than Sip1Aa. Sip153-248 and Sip158-243 were the most stable compared to Sip1Aa, followed by Sip149-251 and Sip178-314. The insecticidal activity of Sip153-248 (Sip158-243) was 2.76 (2.26) times higher than that of Sip1Aa. The insecticidal activity of Sip149-251 and Sip178-314 did not differ significantly from that of Sip1Aa. Basic structural properties, physicochemical properties, and the spatial structure of the mutation site of Sip1Aa and the mutant proteins were analyzed. These results provide a molecular basis for using Sip1Aa to control Coleopteran insects and contribute to the study of the Sip1Aa insecticidal mechanism.